Assessing the influence of education attainment on the performance of small business entrepreneurs in Thailand and New Zealand / Chris Batstone, Geoff Perry and Pussadee Polsaram - Batstone, Chris; Perry, Geoff; Polsaram, Pussadee (2600-7568 Universiti Teknologi MARA Cawangan Pahang, 2006)
The influence of education on the performance of entrepreneurs has been the focus of much discussion and debate amongst entrepreneurship researchers. Most of the formal studies on this topic have been undertaken in the USA and overall they find that the anecdotal stories of the successful poorly educated entrepreneur are the exception rather than the rule. In fact these studies find that education has been an important determinant of entrepreneurial success. Due to the recognition of the importance of entrepreneurship to a country’s development by policy makers throughout the world, and the consequent desire to create education programs and economic conditions that promote entrepreneurship, an international comparison of the contribution of entrepreneur education to business success is worthwhile. This paper compares the importance of entrepreneur education in the performance of New Zealand and Thailand small businesses. The findings suggest that in these two countries entrepreneur education may be negatively correlated with small business performance. A number of explanations for the result are proposed and suggestions for further research outlined.